Patterns of Plant Community Formation and Vegetation Structure in the Afro-Alpine Vegetation of Simien Mountains National Park, Ethiopia - Melese, Getahun Tassew; Tsegay, Berhanu Abraha; Kassa, Getinet Masresha; Kuratie, Getnet Belay (The International Journal of Biotechnology, 2018)
This study was conducted in Simien Mountains National Park, Northwest Ethiopia with the objective of evaluating the patterns of plant community formation and vegetation structure in the afro- alpine vegetation. The data were collected from stratified mountains by using systematic sampling in each stratum from October to November 2015. A total 62 (20 m x20 m) main plots were sampled. In each main plot five (1m x1m) subplots, one at each corner and one at the center, were used to collect data for herbaceous species. In each plot, data on plant species identity, abundance, height and Diameter at Breast Height (DBH) were recorded. Collected specimens were identified at field and also at National Herbarium, Addis Ababa University. Plant community analysis was performed using R version 3.1.3. Sorensen’s similarity coefficient was used to detect dissimilarities among communities. Shannon - Wiener diversity index was computed to describe species diversity of the plant community types. Results showed that a total of 86 plant species representing 34 families and 63 genera were recorded from which90.7 % were herbs, 7% shrubs and 2.3 % trees. Asteraceae is the species richest family whereas Poaceae is the dominant. Three plant community types were recognized from cluster analysis. Species richness, diversity and evenness varied among the plant communities. Analysis of population structure of the dominant species revealed various patterns. Because this afro-alpine area has varied habitat heteroginity, separate plant community regimes need separate planning and implementing (management) measures for sustainability of the vegetation.